Amine functionalised SBA-15 for DAC - Data Set - Wadi, Basil; Golmakani, Ayub; Nabavi, Seyed Ali; Manovic, Vasilije (Cranfield University, 2021)
Raw Data Set accompanying scientific article titled: Evaluation of Moderately Grafted Primary, Diamine, and Triamine Sorbents for CO2 Adsorption from Ambient Air: Balancing Kinetics and Capacity Under Humid Conditions
Keywords: 'Amine'; 'SBA-15'; 'Carbon capture and storage (CCS)'; 'air capture'; 'adsorption'; 'Chemical Engineering not elsewhere classified'